Tea polyphenols improve the memory in aging ovariectomized rats by regulating brain glucose metabolism in vivo and in vitro - Luping Zhang (Elsevier, 2021)
Tea polyphenols (TP) are the main active components of tea. In our study, the effect of TP on the menopause and aging related memory decline and the mechanisms focused on the brain glucose metabolism were clarified. In vivo, ovariectomy (OVX) combined with D-galactose (D-gal) injection were used to establish the memory decline model. TP administration improved the spatial memory by increasing the expressions of GLUT1, 3 and Tau protein O-GlcNAc glycosylation, decreasing Tau hyper-phosphorylation and the Aβ1-42 level, and improving the morphology of mitochondria in hippocampus. Furthermore, in vitro, PC12 cells were treated with Aβ1-42 and EGCG treatment regulated the mitochondrial respiratory function and glycolytic functions, improved the activities of the key enzymes in glycolysis and tricarboxylic acid cycle, increased the SOD activity and decreased the MDA levels in cells. Our study suggests that TP improve the memory in aging ovariectomized rats by regulating brain glucose metabolism.